NUTRITIONAL AND EXTRACTABLE OIL PROFILE IN SEEDS OF SESAMUM INDICUM L. AND MORINGA OLEIFERA LAM. GROWN IN SOKOTO, NIGERIA - Ibrahim Umar KARAYE; Sa’idu Muhammad MAISHANU; Sule Aliyu ANKA; Abubakar SHEHU; Shafi’u Isma’ila ADILI; Lawal Hannatu MUHAMMAD; Aisha MUSA (Journal of Plant Development, 2022)
Nutritional and extractable oil profile in seeds of Sesamum indicum L. and Moringa oleifera Lam. were investigated using standard biochemical procedures. Proximate analysis revealed % crude protein contents of 24.32% in S. indicum while M. oleifera had 27.66%. Crude lipid contents were analyzed and 47.78% was obtained in S. indicum while 28.87% was obtained in M. oleifera. Crude carbohydrate analysis revealed S. indicum with 37.89% while in M. oleifera, it was 34.51%. Crude fibre obtained was 11.32% in S. indicum while 9.37% was identified in M. oleifera. Higher ash content of 9.13% was obtained in M. oleifera while 7.62% was obtained in S. indicum. Available energy (k/cal.) was analyzed in the samples with obtained values in S. indicum 692.22 k/cal. While M. oleifera had 545.91 k/cal. With significant difference (P=0.05) between the two species in terms of available energy (k/cal.). Results of extractable oil profile of S. indicum and M. oleifera revealed appreciable amounts of the oil with 54.65% found in S. indicum while M. oleifera had 39.33% with significant difference (P=0.05) between the two species. Physico-chemical properties of the seed oils analyzed include, acid value determined with 34.32 mg KOHg-1 for S. indicum and 29.98 mg KOHg-1 obtained in M. oleifera. Saponification value of the two samples indicated that S. indicum had 148.82 mg KOH/g while M. oleifera had 127.88 mg KOH/g. Kinematic viscosity was determined and S. indicum had 0.97 mm2/s while 0.78 mm2/s was identified in M. oleifera. Iodine value was determined and S. indicum had 128.56 g l2 /100 g while M. oleifera had 103.68 g l2/100 g. Specific gravity was determined with 0.89 g/cm3 obtained in S. indicum while 0.84 g/cm3 was obtained in M. oleifera. Cetane number was determined; S. indicum had 34.00 while 30.00 was obtained in M. oleifera. Oil colour was determined and the colour ranged from yellowish-brown to creamy-yellow for S. indicum and M. oleifera respectively with no significant difference (P=0.05) in iodine number, acid value, kinematic viscosity and cetane number. State of the oil at room temperature indicated that the oils from the two seed types are liquid at room temperature. Mineral analysis of the two samples indicated that they comprise of appreciable amounts of minerals with phosphorus 385.51±4.96 mg / 100 g obtained in M. oleifera while in S. indicum, 254.54±4.06 mg / 100 g was obtained. Calcium was richly obtained in the two samples with 95.20 mg / 100 g obtained in M. oleifera while 66.70 mg / 100 g was obtained in S. indicum. However, potassium, manganese, copper, and magnesium were appreciably contained in the seeds with significant difference (P=0.05) between the two samples. Thus, it can be recommended that seeds of M. oleifera especially and that of S. indicum should be properly incorporated in the diets especially in the developing countries where hunger and malnutrition ravage the growing children and pregnant women.